Explicitly controlling electrical current density overpowers the kinetics of the chlorine evolution reaction and increases the hydrogen production during seawater electrolysis. (12th February 2023) - Koster, John W.; Tornøe, Søren A.; Kobayashi, Nobuhiko P.; Potts, Donald C.
Abstract: The chlorine evolving reaction (CER) subdues the oxygen evolving reaction (OER) during seawater electrolysis, and impedes hydrogen production without generating harmful chlorine byproducts. We describe a new approach to suppressing CER and increasing the hydrogen production rate by highlighting its distinctive features: using electrical current densities J c > 10 A cm −2 that are much larger than the 1 A cm −2 currents conventionally employed; and using consumable graphite rod-shaped electrodes. Our approach creates a practical means for reaching an electrochemical regime where CER is drastically reduced and hydrogen production is substantially increased. Finite element modeling indicates the rapid reduction in CER is associated with establishing a steep gradient in the electric field between the electrodes. Our study suggests that explicitly elevating J c to more than 10 A cm −2 creates opportunities for creating hydrogen for use in large-scale and industrial applications by reducing CER to negligible levels – an environmental incentive – while increasing the OER and hydrogen production – an economic incentive. Highlights: Microscale system for higher than conventional current density electrolysis. CER in seawater electrolysis suppressed with current densities greater than 10 A cm 2 . Finite-element modeling distribution of electric field between electrodes in seawater. Observed phenomena should scale to larger capacities and industrial implementation. Potential breakthrough in producing non-polluting "Green Hydrogen" from seawater.